Indigenous “Africans” and transnational “PanNetherlanders”: Past and present in the “re-construction” of post-1994 Afrikaner identity - Patrick J. Furlong (Contree, 2012)
This article explores two strategies to “re-imagine” Afrikaner identity in a post-apartheid South Africa in which white Afrikaners, once politically and culturally dominant, have become increasingly marginalized. One, using the early meaning of “Afrikaner” as “African”, claims “indigenous” status, pressing for limited autonomy as an African “tribe,” championing language rights for all Afrikaans-speakers regardless of color, or embracing a larger “African” identity, even joining the ruling African National Congress (ANC). The other seeks to rebuild old links, broken under apartheid, to Flemish and especially Dutch cousins, joined in a pan-Netherlandic community. The article explores how, although in recent times the parochial and essentialist “official” Afrikaner nationalist understanding of Afrikaner “ethnogenesis” had stressed its shaping by the “original” “white” settlers’ struggles with Africans and British latecomers, denying multiracial ancestry and even downplaying broader, European (particularly Low Country) influences, a closer examination shows that that this narrower model long contended with more multicultural and transnational approaches. The evolution of these rival views of Afrikaner identity and responses from the Low Countries and some ANC leaders to these alternative models suggest that such ethnic “re-construction” could help recast Afrikaner self-definition in promising contemporary yet historically grounded terms, provided in the case of pan-Netherlandism that it is not hijacked by the extreme Right, but instead presents Afrikaners as a bridge between Europe and Africa.